2002
DOI: 10.1191/0961203302lu177oa
|View full text |Cite
|
Sign up to set email alerts
|

Serum thrombopoietin levels and anti-thrombopoietin antibodies in systemic lupus erythematosus

Abstract: Thrombocytopenia is a common phenomenon in patients suffering from systemic lupus erythematosus (SLE). The cause of thrombocytopenia in SLE, however, is poorly understood. In this study, 100 patients with SLE were evaluated for serum thrombopoietin levels, anti-thrombopoietin antibodies and routine laboratory parameters such as peripheral blood counts, parameters of blood chemistry and immunologic parameters of SLE. The median platelet count of SLE patients was 230 g/l and 19 were thrombocytopenic (range 8-148… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 29 publications
4
25
3
Order By: Relevance
“…TPO did not correlate with disease activity in our SLE cohort, but did correlate with ECLAM scores and ESR levels in the study by Fureder et al 35 This discrepancy may be due to different TPO assays used or the use of SLEDAI versus ECLAM scoring systems, as ECLAM captures a wider variety of symptoms and incorporates ESR. 43 In agreement with the findings by Fureder et al we also demonstrated a negative correlation between C4 levels and TPO.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…TPO did not correlate with disease activity in our SLE cohort, but did correlate with ECLAM scores and ESR levels in the study by Fureder et al 35 This discrepancy may be due to different TPO assays used or the use of SLEDAI versus ECLAM scoring systems, as ECLAM captures a wider variety of symptoms and incorporates ESR. 43 In agreement with the findings by Fureder et al we also demonstrated a negative correlation between C4 levels and TPO.…”
Section: Discussioncontrasting
confidence: 76%
“…Fureder et al described higher median TPO levels in SLE patients than controls (117 vs. 64 pg/ml) and found that TPO was unrelated to platelet counts. 35 In the current study we also observed higher TPO levels in patients with SLE than in controls, although this did not reach statistical significance, but we confirmed the lack of a relation between TPO and concurrent platelet counts or earlier thrombocytopenia. Assuming normal constant production by the liver, TPO levels are determined mainly by uptake and degradation of TPO by megakaryocytes and platelets, and TPO levels in ITP generally correlate poorly with platelet counts due to compensatory increases in megakaryocyte mass.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Thrombocytopenia has been linked to autoimmune anti-TPO antibodies in a patient with amegakaryocytic thrombocytopenic purpura [34]. Anti-TPO antibodies were observed in 23% of patients (23/100 studied) with systemic lupus erythematosus and thrombocytopenia, and they were generally observed in the patients with more severe thrombocytopenia [35]. In our study of unselected patients with ITP, however, we identified two patients (1%) with circulating inhibitors of TPO activity, using an assay that measures inhibition of a test cell line that is human TPO and/or murine IL-3 dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Fureder [100] was the first to detect naturally occurring autoantibodies against thrombopoietin (anti-TPO) in 23% of SLE patients and correlate their presence with lower platelet counts, but he failed to display a difference in TPO levels. TPO levels, though high compared to normal controls and consistent with disease activity and complement level, did not correlate with platelet count.…”
Section: Thrombopoietin and Anti-thrombopoietin Antibodies: The New Susmentioning
confidence: 99%